THE IMPROVEMENT OF THE STUDENTS’ SPEAKING SKILL OF BALI WIDYA KUSUMA HOTEL SCHOOL THROUGH THREE- STEP INTERVIEW - Ida Ayu Made Sri Widiastuti (Jurnal Santiaji Pendidikan (JSP), 2015)
This present study was a classroom action research which was conducted to overcome the students’ problem in mastering speaking skill by implementing Three- Step Interview. The subject of this study was the first semester students of Bali Widya Kusuma Hotel School. There were two cycles in which every cycle consisted of two sessions. The research was started by administering the initial reflection. In accordance to the main objective of this study, the initial reflection was intended to establish the real pre existing speaking skill mastery of the subjects under study in English. Based on the result of the pre-test which was carried out in the pre-cycle, showed that the subjects’ skill in speaking was categorized as insufficient, which was 54.48. From the technique implemented, there was significant improvement from the subjects’ skill in speaking, in which it improved from insufficient to good, which was 68.09 in cycle I and 76,29 in cycle II. This research furthermore showed there was changing learning behavior as the result of the positive responses concerning the technique applied in improving the subjects’ speaking skills. To sum up, the present clasroom action study proved that the implementation of three-step interview could improve speaking skill in the first semester students of Bali Widya Kusuma Hotel School.